Comparison of clinical efficacy of different internal fixation methods in older adult patients with osteoporotic fractures of proximal humerus - Wang, Zongpu; Wang, Tienan; Qin, Song; Wang, Jianchuan (Frontiers in Surgery, 2025)
ObjectiveTo compare the efficacy of three treatment methods for older adult patients with osteoporotic proximal humerus fractures: proximal humerus locking plate (PHILOS) combined with calcium sulfate injection, PHILOS plate alone, and artificial hemi-shoulder joint replacement.MethodsThe clinical data of 48 older adult patients with osteoporotic proximal humerus fractures admitted to the Shoulder and Elbow Surgery Department of Zhongshan Hospital Affiliated with Dalian University from February 2018–August 2021 were retrospectively analyzed. The patients comprised 18 males and 30 females, with a mean age of (68.6 ± 5.8) years. The 48 patients were divided into three groups based on their treatment methods: Group A: 16 patients treated with PHILOS plate combined with calcium sulfate injection. Group B: 16 patients treated with the PHILOS plate alone. Group C: 16 patients treated with artificial hemi-shoulder joint replacement. Key parameters such as operation time, blood loss, incision length, operation cost, and shoulder joint motion at the final follow-up were recorded and compared. Shoulder joint function was evaluated using the American Shoulder and Elbow Surgeons (ASES) score, Visual Analogue Scale (VAS) for pain, University of California Shoulder Joint Score (UCLA), and Brief Shoulder Function Test (SST).ResultsThere were no statistically significant differences in the preoperative general data between the three groups (P > 0.05), indicating comparability. There was no significant difference in operation time, blood loss, and incision length among Groups A, B, and C (P > 0.05). However, Group C had significantly higher operation costs compared to the other two groups (P < 0.05). At the final follow-up, there were no significant differences in shoulder flexion and rotation among the three groups (P > 0.05). However, a statistically significant difference in abduction was observed between Group A and Group C (P < 0.05). No significant differences were found in ASES, VAS, UCLA, and SST scores among the three groups at the last follow-up (P > 0.05).Complications occurred in 1 patient (Group A), 3 patients (Group B), and 4 patients (Group C), showing a statistically significant difference among the groups (P < 0.05).ConclusionAll three surgical methods are effective in treating older adult osteoporotic proximal humerus fractures, as they significantly alleviate pain and restore joint function. However, the use of a PHILOS plate combined with calcium sulfate injection (Group A) is particularly effective, demonstrating reliable clinical efficacy with fewer complications.